A Functional Variant of SMAD4 Enhances Thoracic Aortic Aneurysm and Dissection Risk through Promoting Smooth Muscle Cell Apoptosis and Proteoglycan Degradation - Ying Wang; Hao-Yue Huang; Guang-Liang Bian; Yun-Sheng Yu; Wen-Xue Ye; Fei Hua; Yi-Huan Chen; Zhen-Ya Shen (EBioMedicine, 2017)
Recent studies indicate important roles for SMAD4 in SMCs proliferation, extracellular matrix maintenance, and blood vessel remodeling. However, the genetic effects of SMAD4 in the pathogenesis of thoracic aortic aneurysm and dissection (TAAD) are still largely unknown. Here we identified a functional variant of SMAD4 which might be involved in the pathological progression of TAAD. Five tagging SNPs of SMAD4 were genotyped in 202 TAAD cases and 400 controls using MALDI-TOF. rs12455792 CT or TT variant genotypes was associated with an significantly elevated TAAD risk (adjusted OR = 1.58, 95%CI = 1.09–2.30) under a dominant genetic model. It was located in the 5’UTR and predicted to influence transcription activity and RNA folding of SMAD4. In luciferase reporter assay, rs12455792 T allele markedly decreased luciferase activities. Accordingly, SMAD4 expression in tissues was lower in patients with CT or TT genotypes, compared with CC. Movat's pentachrome showed that rs12455792 T allele enhanced SMCs loss and fibers accumulation. With angiotensin II induction, rate of Apoptotic SMCs was significantly higher while SMAD4 silenced. Moreover, rs12455792 T allele also increased Versican degradation via ADAMTS-4. In conclusion, this variant might promote SMCs apoptosis and proteoglycans degradation, and further facilitate the progress of TAAD. Our findings identified rs12455792 as a predictor for progression of vascular media pathological changes related thoracic aortic disorders.